Interface adhesion assessment of composite-to-metal bonded joints under salt spray conditions using peel tests. (15th March 2017) - Teixeira de Freitas, S.; Banea, M.D.; Budhe, S.; de Barros, S.
Abstract: An experimental study has been carried out to assess the adhesion quality of composite-to-metal bonded joints under salt spray ageing conditions. The tests were performed according to the ASTM standard of floating roller peel tests with a new specimen layup. The layup and geometry of the specimen was defined in order to have the Carbon Fiber Reinforced Polymer (CFRP) and carbon steel as the rigid and flexible substrate, respectively. Specimens were exposed to salt spray (or salt fog) for 30 and 90 days. The results show that the adhesion performance (i.e. average peel load) of the joints progressively decreases with increasing the ageing time. The fracture surfaces of dry specimens (non-aged) exhibit a cohesive failure within the adhesive layer, which indicates a good adhesion between the CFRP-steel interfaces. Interface degradation is indicated by a drop in peel load and adhesive failure. The percentage of adhesive failure increases with ageing times. Fracture surfaces of the adhesive failure exhibit deposition of NaCl crystal at the interface. Peel test successfully assessed the interface adhesion in aged and non-aged conditions, and can be used as a fast, easy and reliable test to study the long term durability in case of composite-metal bonded joints.